Comparative Analysis of Herding Behavior in Indonesia, Malaysia, and Singapore - Ramadhansyah, Adji; Rokhmawati, Andewi; Fitri, Fitri; Yafiz, Ifa A (Program Pascasarjana, Universitas Riau, 2020)
Herding Behavior is an investor bias that affects stock market price. Stock market is one of the factors that can influence economic condition in a country. This research examine the phenomenon of herding behavior in Indonesia, Malaysia, and Singapore from 2016 to 2019. This research used secondary data, stocks return and market return, and transformed it into Cross Sectional Absolute Deviation (CSAD) to test the dispersion level of stock return to find herding behavior indication using quantile regression. This research also comparing herding behavior between Indonesia and other two countries using independent sample t test. Result showed that in all countries there were no indication of herding behavior in all kind of market condition. This research also found the difference of herding behavior between Indonesia and other countries.